The Urgency of Waqf Land Certification in Ensuring Legal Certainty of Land Rights - Aisyah, Aisyah (Ipso Jure, 2025)
The prevalence of uncertified waqf land in Indonesia shows the weak legal protection of religious assets in the national land system. The absence of a certificate makes waqf land vulnerable to disputes, unauthorized transfer of rights, and difficulty in proving legal status in court. This study aims to examine the normative aspects of waqf land certification and its urgency in ensuring legal certainty. The method used is a legislative and conceptual approach, by analyzing regulations such as Law No. 41 of 2004 concerning Waqf, Law No. 5 of 1960 concerning Agrarian Principles, and Government Regulation No. 24 of 1997 concerning Land Registration. The results of the study show that although the legal norms of waqf are available, their implementation has not been effective due to the disharmony between the waqf law and the national land system. Waqf land certification should not only be seen as an administrative obligation, but also as a juridical instrument for the protection of waqf assets. Regulatory harmonization and institutional coordination between the Ministry of Religion and BPN are needed, including the integration of digital systems such as SIWAK and PTSL. Thus, waqf land certification is a strategic step in realizing a national legal system that is fair, integrated, and responsive to religious and social values.